EFFECTS OF THEATER IN THE PRISON ENVIRONMENT: BETWEEN PRISONINIG AND PERSONAL RECONSTRUCTION - Adolf MOTE; Jean Pierre MBAME; Fride NGUIDJO (Universitaria Publishing House, Craiova, 2022)
What are the effects of the theater, as an educational environment, that influence not the prisonerization, but the personal reconstruction of the prisoner in the social and cultural environment in which the prisoner finds himself? The observation is that the state of prisonization of the minor prisoner accentuates his precariousness and mortgages his personal reconstruction. The objective of this study is to analyze the effects of theater as a transitional area of creativity. The research is part of the comprehensive paradigm and has opted for a qualitative approach. The research was addressed to 10 participants of the "thirteen quarter" of the Central Prison of Yaoundé. The data collected and processed through the interview guide made it possible to arrive at the results according to which the place of the theatrical act in the prison environment favors a repositioning of identity.